A risk mitigation approach for concurrent engineering projects. (8th July 2008) - Kayis, Berman; Ahmed, Ammar; Amornsawadwatana, Sataporn
Generally, risks are encountered and generate negative outcomes in concurrent engineering (CE) projects including project delays, cost overruns and unacceptable quality. These outcomes can be avoided by establishing a systematic risk management process. In this research, a risk management approach used is outlined, according to Australia and New Zealand risk management standard (AS/NZS 4360: 1999). An IDEF3 model is used to represent the CE project architecture as a process model. A risk assessment and mitigation model is developed to identify, assess and evaluate risks in concurrent engineering projects to suggest a mitigation strategy. Five heuristic rules are implemented in three simulated scenarios and genetic algorithm is bound to generate the most cost-effective solutions. The risk mitigation model developed in this research is aimed to be used as a decision support tool for project managers to select the best mitigation strategy based on the available mitigation budget and objectives of the project.